A Comparative Study of Tooth Size and Dental Arch Dimensions between Iraqi Arabs and Kurds with Class I Normal Occlusion - Alaa D Mahmood (University of Mosul, College of Dentistry, 2012)
Aims: To search for any differences in tooth size and dental arch dimensions between Iraqi Arabs and Kurds. Materials and Methods: Upper and lower dental casts of 40 Kurdish and 40 Arabic subjects ranging in age between 14-18 years and equally divided between males and females, were measured for mesiodistal tooth size as well as for dental arch width, length and perimeter. Results: Kurdish males and females showed larger values for mesiodistal tooth size and dental arch width, perimeter and length than their Arabic counterpart. The majority of differences were significant. Males in both Arabic and Kurdish population had greater tooth and dental arch size than females. Conclusions: Data of tooth size and dental arch dimensions for Iraqi Arabs is not applied to Iraqi Kurdish subjects.